PERAN DAYCARE DALAM STIMULASI PERKEMBANGAN FISIK MOTORIK ANAK USIA 2-3 TAHUN DI DAYCARE KEPIK KUNING TANGERANG SELATAN - leny leny leny; Indro Wiyarno; Syafwandi (Universitas Ngudi Waluyo, 2023)
Stimulation of physical and motoric development is very important for children aged 2-3 years, because this affects the quality of optimal growth and development in the future. The proper and good physical development is determined by how the stimulation and early detection in the physical development phase of the children in accordance with the stage of development of their ages. However, the parents daily work, creates an affect in the stimulation process for children. Therefore, many parents entrust their children in daycare. Through the background of the problem above, the authors conducted a study to find out how the role of daycare in stimulating physical motor development, especially for children aged 2-3 years in Daycare Kepik Kuning. The method used in this research is descriptive research method. This research was carried out for three months. The research subjects or informants who became the source of information in this study were elements of daycare institutions which included the principal, educators/caregivers, pupil and parents at Daycare Kepik Kuning. From the results of the study, it was found that there was a positive change in behavior and an increase in physical motoric skills in children who participated in the service program at the daycare Kepik Kuning. This means that the daycare Kepik Kuning has played an important role in the process of achieving physical motoric development in children aged 2-3 years.